Complexities of cultural difference in social care work in England. Issue 5 (3rd September 2017) - Willis, Rosalind; Pathak, Pathik; Khambhaita, Priya; Evandrou, Maria
ABSTRACT: The ageing of the ethnic minority population in Britain has led to a more ethnically diverse older client group for social care services than has ever been the case. This article focuses on the issue of how social care staff in England experience working across differences of culture, ethnicity, religion, and language. First, the article critically discusses the concept of cultural competence. Then, it reports on the perspectives of social care staff on their attempts to work in a culturally competent way. Individual in-depth qualitative interviews were carried out with 39 social care practitioners, and thematically analysed. Themes related to professional competence, appropriate behaviour, and training needs. Some practitioners felt unable to perform to their accustomed skill level when working across diversity, which has implications for the quality of care provided and job satisfaction. Other practitioners were confident in working across diversity. The key difference between these practitioners was a degree of cultural reflexivity. Recommendations for training are provided.